Advancing Professional Learning in Libraries: An Exploratory Study of Cataloging and Metadata Professionals' Experiences and Perspectives on Continuing Education Issues. Issue 3 (3rd April 2017) - Park, Jung-ran; Tosaka, Yuji
ABSTRACT: Based on a set of web survey data, this study examines cataloging and metadata professionals' perspectives on issues surrounding continuing education. The results show that emerging data standards such as the Semantic Web and BIBFRAME, as well as metadata and digital library-related topics, are subject areas currently central to their professional concerns, in addition to RDA, for professional development. Topics such as ontologies, social tagging, and automatic metadata generation were rarely reported. Meaningful interactions were often found to be lacking in online education. The results provide evidence of the need to expand the pool of shared expertise to meet our collective needs for continuing education in the cataloging and metadata community.